2012
DOI: 10.3109/09273948.2012.748080
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 and Clinical Features of Acute Anterior Uveitis in Cuba

Abstract: Results from this study are similar to data described in other countries. HLA-B27 allele distribution in controls is lower than other reports in Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…43 In a Chinese cohort, in addition to male preponderance, a younger age of onset was observed among male patients with HLA-B27-associated uveitis compared to females. Interestingly, male sex was also associated with increased risk of vision loss in a recent cohort in USA, 45 whereas another study from the Netherlands that focused on differences in outcomes based on gender indicated no gender differences in vision loss among HLA-B27-associated anterior uveitis patients.…”
Section: Non-infectous Uveitidesmentioning
confidence: 95%
“…43 In a Chinese cohort, in addition to male preponderance, a younger age of onset was observed among male patients with HLA-B27-associated uveitis compared to females. Interestingly, male sex was also associated with increased risk of vision loss in a recent cohort in USA, 45 whereas another study from the Netherlands that focused on differences in outcomes based on gender indicated no gender differences in vision loss among HLA-B27-associated anterior uveitis patients.…”
Section: Non-infectous Uveitidesmentioning
confidence: 95%
“…Ocular complications in HLA-B27-associated AU are diverse, and include commonly posterior synechiae, cataract, ocular hypertension, or glaucoma and hypotony (Table 3) . 25,30,31,34,35,39,60 Epiretinal membrane and band keratopathy can occur, but are less frequent. The incidence rate of any ocular complication was 0.22/ eye-year, which is lower than in other uveitis entities, such as juvenile idiopathic arthritis-associated uveitis or uveitis associated with Behcet disease.…”
Section: Visual Outcomes and Complicationsmentioning
confidence: 99%
“…Studies which include AU or AAU patients solely, usually indicate a higher frequency of HLA-B27-associated uveitis of approximately 33-67% across different racial groups, except in one study from Saudi Arabia, in which HLA-B27-associated uveitis was only 0.6% (Table 2) . 5,[30][31][32][33][34][35][36][37] In addition to genuine differences, these distinctions might be a consequence of variable referral to tertiary centers and might be also influenced by an inconsistent work-up for uveitis, including the testing for HLA-B27. Similarly, the frequency of systemic disease associated with HLA-B27associated uveitis seems to be lower in Japan (1.3%), India (15%), and Thailand (15%) when compared with Western countries (~50%).…”
mentioning
confidence: 99%
“…The HLA-B27 is considered to be strongly associated with both AAU and AS [5, 8, 10, 14]. Recent genetic studies have revealed that five candidate genes in the JAK-STAT signaling pathway were considered genetic predisposing factors for different autoimmune-mediated diseases [3845].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the occurrence of AAU is associated with the prognosis of ankylosing spondylitis (AS) [6, 7]. The frequency of AAU, which is characterized by positive human leukocyte antigen- (HLA-) B27, varies across different ethnic populations [810]. In the United States and Western Europe, the prevalence of HLA-B27 with AAU is up to 50% [5, 8, 11].…”
Section: Introductionmentioning
confidence: 99%